2014
DOI: 10.1111/ics.12120
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative evaluation method of skin texture affected by skin ageing using replica images of the cheek

Abstract: This study suggests that visual grading of skin texture score based on new facial skin texture index and quantification of star configurations will be useful in evaluating skin ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…6), thus it deserved special attention. Ryu et al [12] have shown through the use of skin replicas that the number of 'star configurations' (intersections) on left cheek skin decreases with age, a result that agrees with our data. To verify the accuracy of the automatic detection and calculation of intersections in our study, we also counted the intersections manually.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…6), thus it deserved special attention. Ryu et al [12] have shown through the use of skin replicas that the number of 'star configurations' (intersections) on left cheek skin decreases with age, a result that agrees with our data. To verify the accuracy of the automatic detection and calculation of intersections in our study, we also counted the intersections manually.…”
Section: Discussionsupporting
confidence: 92%
“…The microscopic appearance of the skin surface was a net-like structure which was composed of primary and secondary lines [12]. These lines intersected each other to form polygons (grids) and intersections.…”
Section: Texture Featuresmentioning
confidence: 99%
“…To date, investigations into aging that estimate skin age in living subjects have been performed using the face, back of hand, or neck, which are all areas exposed to sunlight . Based on the results of the present study, measuring texture and roughness of unexposed skin eliminates the effects of sunlight exposure and shows the general age‐associated changes for an individual, while measuring erythema of exposed skin shows age‐associated changes that also encompass the effect of sunlight.…”
Section: Discussionmentioning
confidence: 85%
“…With aging, the ridges increase in size, become distorted, and disappear . The number of cross‐hatches therefore decreases with age, leading to a smaller texture value with increasing age . The roughness parameter changes due to aging‐associated atrophy of the structural components of skin tissue .…”
Section: Discussionmentioning
confidence: 99%
“…노화가 진행됨에 따라 1차 라인은 깊고 넓어지며 2차 라인은 사라지면서 두 라인 사이의 연결이 불규칙적으로 변화되어 피부 미세구조는 다양 한 형태로 뒤틀리거나(distortion) 변형(deformation)되어 사라지게(disappearance) 된다 [5]. 이러한 피부 표면 미 세구조의 변화는 피부의 표면에서 반사되는 빛에 변 화를 주어 윤기가 없어지고 피부 톤이 칙칙해지는 등 피부 노화 현상을 일으키게 된다 [6].…”
unclassified